An Investigation on Factors Influencing Satisfaction and Loyalty of Online Shopping Customers in China - Yu, Jianghong (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study investigates the factors influencing customer satisfaction and loyalty in online shopping among Chinese consumers, focusing on the impact of response, security and privacy, payment methods, and disconfirmation of information, service, and product quality on customer satisfaction and loyalty. Research design, data and methodology: A quantitative methodology was adopted, utilizing data collected from 550 online shoppers in China through a structured questionnaire. Multiple regression analysis and Structural Equation Modeling (SEM) were employed to examine the relationships between the variables. Results: The analysis indicates that all proposed constructs were positively correlated with online shopping customers’ satisfaction and loyalty. Among these factors, product quality, security/privacy and service quality have the most significant influence on satisfaction, which, in turn, indirectly affects customer loyalty. Conclusions: This study highlights key factors influencing customer satisfaction and loyalty in China’s e-commerce, emphasizing the practical importance of secure transactions, efficient payment processes, accurate information, and responsive service. The findings underscore overall satisfaction as a critical mediator, guiding businesses to optimize service quality for long-term customer retention. By aligning with emerging trends in China’s digital economy, this research contributes to the literature on e-commerce growth, offering actionable insights for enhancing competitive advantage.